2015
DOI: 10.1038/srep10001
|View full text |Cite
|
Sign up to set email alerts
|

Rice (Oryza sativa L) plantation affects the stability of biochar in paddy soil

Abstract: Conversion of rice straw into biochar for soil amendment appears to be a promising method to increase long-term carbon sequestration and reduce greenhouse gas (GHG) emissions. The stability of biochar in paddy soil, which is the major determining factor of carbon sequestration effect, depends mainly on soil properties and plant functions. However, the influence of plants on biochar stability in paddy soil remains unclear. In this study, bulk and surface characteristics of the biochars incubated without rice pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(30 citation statements)
references
References 47 publications
1
24
0
Order By: Relevance
“…A previous study reported that fresh C supply would decrease stability of old SOC in deep soil layers through priming (Fontaine et al, 2007). A recent study reported increased biochar-C incorporation into soil microbial biomass with rice plants (Wu et al, 2015), but it was uncertain whether this positive response was related with LMW-C exudates from rice roots. LMW-Cs support microbial growth and account for as much as 30% of total soil respiration ( van Hees et al, 2005), which play both a direct and an indirect role in the formation, decomposition, and stabilization of soil C storage (de Graaff et al, 2010).…”
Section: Introductionmentioning
confidence: 98%
“…A previous study reported that fresh C supply would decrease stability of old SOC in deep soil layers through priming (Fontaine et al, 2007). A recent study reported increased biochar-C incorporation into soil microbial biomass with rice plants (Wu et al, 2015), but it was uncertain whether this positive response was related with LMW-C exudates from rice roots. LMW-Cs support microbial growth and account for as much as 30% of total soil respiration ( van Hees et al, 2005), which play both a direct and an indirect role in the formation, decomposition, and stabilization of soil C storage (de Graaff et al, 2010).…”
Section: Introductionmentioning
confidence: 98%
“…The FTIR spectra of the biochar peak at 1580 cm -1 which corresponded to the C=O stretching and aromatic C=C vibrations [18]. The peaks at 1444 cm -1 aliphatic C-H groups and C=C stretching and 882 cm -1 were related to aromatic C-H bending, respectively [19,20]. The peak at 1080 cm -1 could be related to the C-O stretching [21].…”
Section: Ft-ir Spectrummentioning
confidence: 98%
“…The last step of the bead samples was related to the burning of the pyrolysis product which was formed during analysis in the N2 atmosphere. FTIR spectrum of the biochar involves peaks related to the C-O group (1111 cm -1 and 1021 cm -1 ) and amine group (1592 cm -1 and 1416 cm -1 ) [18][19][20]. Before 600°C, the TGA analysis was carried out in the inert atmosphere, because neat bead undergoes both decomposition and pyrolysis reaction while biochar does not decompose.…”
Section: Thermogravimetric Analysismentioning
confidence: 99%
“…The biochar decomposition can give the entrapped portion of chemicals exposure to degradation. Therefore, the release of entrapped pesticide from saturated biochar is dependent on the biochar properties and its degree of recalcitrance, the properties of the organic substance, and the environmental conditions (Spokas 2010;Wu et al 2015).…”
Section: Drawbacks Of Biochar Applicationmentioning
confidence: 99%